Analisis Perhitungan Pajak Penghasilan Pasal 21 Dalam Transparansi dan Kepatuhan Perpajakan: (Studi Kasus Pada Sistem Penggajian Dinas Pendidikan dan Kebudayaan Kota Sukabumi) - Nurodin, Idang; Suherman, Acep; Barokah, Nur (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2024)
This study aims to analyze the calculation of Income Tax (PPh) Article 21 at the Sukabumi City Education and Culture Office in the context of tax transparency and compliance, especially after the implementation of the Average Effective Rate (TER) policy in accordance with Government Regulation Number 58 of 2023. This study uses a descriptive qualitative approach with case study methods through interviews, observations, and documentation. The results of the study show that administratively, the implementation of TER is quite effective in simplifying tax calculations through a structured digital system. However, technically there are still challenges, such as fluctuations in Performance Allowances (Tukin) and the complexity of data from various work units that require strict verification. The level of transparency is not optimal because the tax information system is still manual, information disclosure is limited, and there is a lack of education and the unavailability of formal payslips. Meanwhile, institutional compliance has been running according to the provisions, but individual employee compliance is still low due to low tax literacy and delays in reporting tax returns. Therefore, the development of an integrated and educational tax information system, regular distribution of withholding evidence, and continuous socialization programs are needed to improve transparency and overall tax compliance.